1987
DOI: 10.1002/1097-4679(198701)43:1<6::aid-jclp2270430103>3.0.co;2-x
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of PTSD in a national cohort of Vietnam veterans

Abstract: At age 36, Vietnam veterans in the high school class of 1963 reported significantly more problems related to nightmares, loss of control over behavior, emotional numbing, withdrawal from the external environment, hyperalertness, anxiety, and depression than did their classmates matched with them on 5 1 high school characteristics. These problems correspond closely to the disorder labeled post-traumatic stress disorder (PTSD) by the American Psychiatric Association. PTSD was associated with other family, mental… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
64
1
2

Year Published

1989
1989
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 108 publications
(69 citation statements)
references
References 7 publications
2
64
1
2
Order By: Relevance
“…His view is supported by the Jackson (1982) and Wilson (1978) findings, but seems inconsistent with Schnurr et al's (1993) report. The hypothesis that high moral standards reduce the likelihood of participation in atrocities and resulting PTSD symptoms seems consistent with the Hendin and Haas (1984) and Schnurr et al (1993) studies, and with most of the Card (1987) and Watson et al (1988) church going data, but not the Watson et al (1988) findings on reported illegal activity. Card's (1987) data on arrests seem consistent with either position.…”
supporting
confidence: 81%
See 3 more Smart Citations
“…His view is supported by the Jackson (1982) and Wilson (1978) findings, but seems inconsistent with Schnurr et al's (1993) report. The hypothesis that high moral standards reduce the likelihood of participation in atrocities and resulting PTSD symptoms seems consistent with the Hendin and Haas (1984) and Schnurr et al (1993) studies, and with most of the Card (1987) and Watson et al (1988) church going data, but not the Watson et al (1988) findings on reported illegal activity. Card's (1987) data on arrests seem consistent with either position.…”
supporting
confidence: 81%
“…The Vietnam Veterans Questionnaire Combat Exposure Scale (CES; Figley & Stretch, 1980), the Revised Defining Issues Test (DIT; Rest, 1979a), and the Posttraumatic Stress Disorder Interview (PTSD-I; Watson, Juba, Manifold, Kucala, and Anderson, 1991) were administered to 85 male Vietnam war veterans, all of whom reported combat experience. Seventy-three of these men were in treatment at the St.…”
Section: Subjectsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, this study suggests that the relationship between development of PTSD and level of combat exposure is not as clear as previously believed. Factors other than combat, such as childhood trauma (38,39) and preexisting personality (37,(40)(41)(42), may also play an important part in symptom development. Successful treatment of combatrelated PTSD requires a clear understanding of the relative etiologic contributions of both combat and noncombat factors.…”
Section: Discussionmentioning
confidence: 99%